Developing instrument to measure the use of online comic as educational media - Radeswandri Radeswandri; Afiq Budiawan; Rian Vebrianto; Musa Thahir (Journal of Education and Learning (EduLearn), 2021)
Studies related to the development of instruments to measure the use of online comics as an educational media in tertiary institutions are still limited. A survey study was carried out on 60 students from various study programs at open university. The data collection was done using an online questionnaire. The data were analyzed using quantitative data analysis assisted by SPSS version 23.00 for Windows. The results of this study showed that: 1) the preparation and development of an evaluation instrument for the use of online comics for students was carried out using a theoretical development model to test seven research constructs; 2) the results of the construct validity and reliability testing indicated that the validity of the evaluation instrument for the use of online comics for students met the valid criteria because the value of r-count more than r-table (r-count more than 0.254); and 3) the reliability of the online comic use evaluation instrument for students that had been compiled and developed in this study also fulfilled the high category as indicated by the alpha Cronbach reliability coefficient of 0.980. This indicates that the instrument developed meets the requirements to be used in measuring the use of online comics for students.